A cocriação de valor no ambiente universitário: um estudo sobre os efeitos da satisfação, lealdade e confiança - Vieira, Viviana Beatriz Huespe Aquino (2017)
The co-creation of value is an emergent concept in marketing area whose focus acts over the interaction consumer – company. According to Prahalad and Ramaswamy (2004a), consumers seek for high quality interaction which enable them to co create unique experiences with the firm once the passive role they had had was left behind and a new and more active position was assumed in relation to the availability of information, internet and the desire of experiencing. From Prahalad and Ramaswamy surveys (2004a, 2004b, and 2004c), a lot has been developed and discussed with the aim of better understanding the background, moderators, processes and consequential which influence the consumer behavior into the co-creation of value. In this context, this piece of work had as its main target to analyze the influence of satisfaction, fidelity and confidence of the students as background for co-creation value in the field of higher public education seeking to answer the relations between these variables. Since it is a theory under construction, the achievement of empirical research remains as one of the priorities of the marketing agenda, and the educational environment has been chosen because it is considered an example of co-creation, in which students and teachers interact and such interaction can generate accomplishment and high value for everyone involved. From the perspective of university management the understanding of the dynamics of co-creation of value can provide insights into the definitions of strategies which lead to the accomplishment of the institutional targets. This survey was conducted with the use of a questionnaire applied personally in various groups of students from a university. The date was analyzed statistically both in correlation and regression, which pointed the existence of moderated positive correlation among every and each of the variables surveyed, besides the confirmation of the hypothesis tested which aimed into the direct and positive influence of the variables “satisfaction”, “fidelity” and “confidence” to the variable “co-creation of value”. The conclusion of the work aims into the applicability of the model to the context surveyed, or rather, it shows that practicing the satisfaction, fidelity and confidence of the students may create a friendly atmosphere in which unique experiences of co-creation of value occur bringing benefits to all the involved in the process.